Pidana Mati atas Permufakatan Jahat dalam Kejahatan Narkotika: Analisis Putusan PN Medan No. 1957/Pid.Sus/2023/PN Mdn - Angga Prasetya (Albayan Journal of Islam and Muslim Societies, 2024)
Criminal conspiracy (samenspanning) in narcotics offenses has become a crucial issue in Indonesian criminal law, particularly when punishable by death penalty. The case of District Court of Medan Decision No. 1957/Pid.Sus/2023/PN Mdn illustrates how the court interpreted the involvement of defendants in an international narcotics network, even though the crime had not yet been fully carried out. This article aims to analyze the juridical grounds for imposing the death penalty in narcotics conspiracy cases and to assess its conformity with justice, legal certainty, and human rights protection. The research applies a normative juridical method through case study analysis, combined with doctrinal review and statutory approaches. Findings indicate that death penalty in narcotics conspiracy often triggers debates between the effectiveness of narcotics eradication and the protection of the right to life, suggesting the need for harmonization between positive law, criminal policy, and international human rights principles.